Celebrating Suprematism. - Lodder, Christina (Russian History and Culture Ser., 2018)
Celebrating Suprematism throws vital new light on Kazimir Malevich's abstract style and the philosophical, scientific, aesthetic, and ideological context within which it emerged and developed. The essays in the collection, which have been produced by established specialists as well as new scholars in the field, tackle a wide range of issues and establish a profound and nuanced appreciation of Suprematism's place in twentieth-century visual and intellectual culture. Complementing detailed analyses of The Black Square (1915), Malevich's theories and statements, various developments at Unovis, Suprematism's relationship to ether physics, and the impact that Malevich's style had on the design of textiles, porcelain and architecture, there are also discussions of Suprematism's relationship to Russian Constructivism and avant-garde groups in Poland and Hungary.